The Readers Community of the Journal “Bulletin of Knowledge” (1903–1918) as an Example of Successful Communication between the Editorial Board and the Audience - O. V. Moreva (Библиосфера, 2023)
The journal “Bulletin of Knowledge“ (1903–1918) was popular in various readership groups, aspiring to self-education. The purpose of the article is to determine the role of the communicative strategy of the editor–publisher of the journal V. V. Bitner for the creation of the community of “Bulletin of the Cognoscenti”, which was a “community of interpreters” (according to S. Fish), within the framework of the history of reading. The sources for the analysis were a set of journals stored in the Sverdlovsk Regional Universal Scientific Library named after V. G. Belinsky (Yekaterinburg), editorial articles, letters from readers, memoirs of V. V. Bitner and his contemporaries. Changes in the volume of the journal’s headings help to trace the history of the creation of a of readers community. The journal had sections to answer subscribers’ questions, as well as headings to publish letters to find friends, requests for help, and discussions of topical contemporary issues. “Discussion branches” of separate topics, continued sometimes for a year or more. Members of the readers’ community also interacted in real life. Their “disvirtualization” took place thanks to the organization of lectures, excursions and congresses of subscribers. The titles of the headings, examples of readers’ letters and the assessment of contemporaries indicate the uniqueness of this educational project. The portrait of V. V. Bitner by I. E. Repin, commissioned by subscribers for the tenth anniversary of the journal, can serve as an evidence of respect and admiration of the editorpublisher work. The commercial success of the “Bulletin of Knowledge” allowed V. V. Bitner to implement other publishing projects.